Association of rs5888 SNP in the scavenger receptor class B type 1 gene and serum lipid levels - Wu, Dong-Feng (BioMed Central, 2012)
BACKGROUND: Bai Ku Yao is a special subgroup of the Yao minority in China. The present study was undertaken to detect the association of rs5888 single nucleotide polymorphism (SNP) in the scavenger receptor class B type 1 (SCARB1) gene and several environmental factors with serum lipid levels in the Guangxi Bai Ku Yao and Han populations. METHODS: A total of 598 subjects of Bai Ku Yao and 585 subjects of Han Chinese were randomly selected from our stratified randomized cluster samples. Genotypes of the SCARB1 rs5888 SNP were determined by polymerase chain reaction and restriction fragment length polymorphism combined with gel electrophoresis, and then confirmed by direct sequencing. RESULTS: The levels of total cholesterol (TC), high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C), apolipoprotein (Apo) AI were lower but ApoB was higher in Bai Ku Yao than in Han (P < 0.05-0.001). The frequencies of C and T alleles were 78.3% and 21.7% in Bai Ku Yao, and 73.7% and 26.3% in Han (P < 0.01); respectively. The frequencies of CC, CT and TT genotypes were 60.0%, 36.6% and 3.4% in Bai Ku Yao, and 54.2%, 39.0% and 6.8% in Han (P < 0.01); respectively. The subjects with TT genotype in both ethnic groups had lower HDL-C and ApoAI levels than the subjects with CC or CT genotype (P < 0.05 for all). Subgroup analyses showed that the subjects with TT genotype in Bai Ku Yao had lower HDL-C and ApoAI levels in males than the subjects with CC or CT genotype (P < 0.05 for all), and the T allele carriers had higher TC, LDL-C and ApoB levels in females than the T allele noncarriers (P < 0.05 for all). The participants with TT genotype in Han also had a lower tendency of HDL-C and ApoAI levels in males than the participants with CC or CT genotype, but the difference did not reach statistically significant (P = 0.063 and P = 0.086; respectively). The association of serum HDL-C and ApoAI levels and genotypes was confirmed by the multiple linear regression analysis in both ethnic groups. Serum lipid parameters were also correlated with several environmental factors. CONCLUSIONS: The differences in serum lipid levels between the two ethnic groups might partially attribute to the differences in the SCARB1 rs5888 SNP and several environmental factors.